Fetal kidney length as a useful adjunct parameter for better determination of gestational age - Ugur, Mete G. (Saudi Med J, 2016)
OBJECTIVES: To determine the validity of fetal kidney length and amniotic fluid index (AFI) in labor dating. METHODS: This prospective study included 180 pregnant women followed up in the outpatient clinic at the Department of Obstetrics and Gynecology, Gaziantep University, Turkey, between January 2014 and January 2015. The gestational age (GA) was estimated by early fetal ultrasound measures and last menstrual period. Routine fetal biometric parameters, fetal kidney length, and amniotic fluid index were measured. We studied the correlation between fetal kidney length, amniotic fluid index, and gestational age. RESULT: The mean gestational age depending on last menstrual period and early ultrasound was 31.98±4.29 (24-39 weeks). The mean kidney length was 35.66±6.61 (19-49 mm). There was a significant correlation between gestational age and fetal kidney length (r=0.947, p=0.001). However, there was a moderate negative correlation between GA and AFI. Adding fetal kidney length to the routine biometrics improved the effectiveness of the model used to estimate GA (R(2)=0.965 to R(2)=0.987). CONCLUSION: Gestational age can be better predicted by adding fetal kidney length to other routine parameters.